Pragmatic functions of political humor used by Egyptian Facebook users - Elshindy, Shereen (AUC Knowledge Fountain, 2019)
Political humor has always been a powerful tool to convey messages of resistance, criticism, sarcasm, etc. The growth of digital tools and social networking sites has provided a new platform for the creation and sharing of political humor. This study explores the functions of political humor employed by Egyptian users of Facebook (FB) in reaction to a number of political events and difficult circumstances through investigating the pragmatic functions of a number of humorous posts published on two satirical public FB pages /portō ṭora min ʔajlika ʔant/ and /sōbar faʃxa/. Fifty-nine posts have been selected for analysis. The selected posts focused on two main themes: The Egyptian presidential elections in 2018, and price inflation, the latter including the subcategories of metro tickets, fuel, vegetables, clothes and others. Results of the study revealed that posts during the elections performed assertion of the lack of real democracy, as well as protest against the bad electoral process. On the other hand, posts addressing price increases performed complaint about the impact on citizens’ life. Furthermore, the pragmatic functions detected in this study show that humor functions as a tool to vent frustration, and to express resistance indirectly in the absence of more direct tools to implement change and express resistance, and in an environment where both the lack of democracy and fear of suppression dominate